A Novel Multi-Functional DSTATCOM with Distribution Generation using FRC Controller - CH. Sri Prakash; G. Kesava Rao; Obbu Chandrasekhar; P. V. Satyaramesh (Institute of Advanced Engineering and Science, 2018)
Distribution Generation plays a significant role in remote areas where the utility grid is affected and initializing by renewable energy sources to acquire the sufficient power demand. In distribution system, it is very exigent consumer related concern which is confronted due to mis-operation of massive non-linear load apparatus. A multi-functional distributed static compensator incorporates the best choice for enhancing the power quality features with effective control scheme under rambled non-linear loads. Conventional control schemes are more adversed with greater switching losses due to extreme harmonic frequencies in a refernce current component. This paper proposes, a novel multi-objective fundamental reference current control scheme based multi-functional DSTATCOM furnishes the current harmonic compensation at PCC, reactive power compensation, power factor correction, active power exchanging, minimizing the switching losses, incredible efficiency and power factor correction. The validation of proposed multi-functional DSTATCOM with proposed control strategy under rated capacity of distribution generation is evaluated by using Matlab/Simulink platform and simulation results are presented.